THE INFLUENCE OF COMPANY IMAGE, SERVICE QUALITY AND PRICE PERCEPTION ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION SU2R TRAVEL BATANG - Fahlefi, Diva Riza; Harminingtyas, Rudika; Susetyarsi, Th; Widowati, Maduretno (STIE Pelita Nusantara Semarang, 2023)
The aim of this research is to analyze the influence of company image, service quality and price perception on repurchase decisions through customer satisfaction. The minimum number of samples used is 100 respondents. The sampling technique is purposive sampling. The analysis tool used is PLS-SEM using SmartPLS software. The results of the analysis can be concluded that: company image has a positive effect on customer satisfaction. Service quality has a positive effect on customer satisfaction. Price perception has a positive effect on customer satisfaction. Company image has a positive effect on repurchase intention. Service quality has a positive effect on repurchase intention. Price perception has a positive effect on repurchase intention. Customer satisfaction has a positive effect on repurchase interest. Customer satisfaction has a partial mediating role between company image and repurchase intention. Customer satisfaction has a partial mediating role between service quality and repurchase intention. Customer satisfaction has a partial mediating role between price perception and repurchase intention.